Use of BRFSS Data and GIS Technology for Rapid Public Health Response During Natural Disasters - James B. Holt, PhD, MPA; Ali H. Mokdad, PhD; Earl S. Ford, MD, MPH; Eduardo J. Simoes, MD, MSc, MPH; William P. Bartoli, MS; George A. Mensah, MD (Centers for Disease Control and Prevention, 2008)
Having information about preexisting chronic diseases and available public health assets is critical to ensuring an adequate public health response to natural disasters and acts of terrorism. We describe a method to derive this information using a combination of data from the Behavioral Risk Factor Surveillance System and geographic information systems (GIS) technology. Our demonstration focuses on counties in states that are within 100 miles of the Gulf of Mexico and the Atlantic Ocean coastlines. To illustrate the flexible nature of planning made possible through the interactive use of a GIS, we use a hypothetical scenario of a hurricane making landfall in Myrtle Beach, South Carolina.